Risk factors for postoperative blood transfusion after shoulder arthroplasty. (June 2022) - Kopechek, Kyle J; Frantz, Travis L; Everhart, Joshua S; Samade, Richard; Bishop, Julie Y; Neviaser, Andrew S; Cvetanovich, Gregory L
Purpose: To identify the effect of surgical indication, patient factors, and perioperative characteristics on transfusion after shoulder arthroplasty (SA). Methods: Shoulder arthroplasties for osteoarthritis (OA) ( N = 47), rotator cuff arthropathy (RCA) ( N = 50), fracture ( N = 76), revision ( N = 66), and periprosthetic joint infection (PJI) ( N = 35) performed at a single institution during a 6-year period were included. All other indications were excluded. Patient-based and surgical risk factors, including surgical indication, for postoperative allogeneic red blood cell transfusion were assessed with multivariate logistic regression analysis. Results: A total of 274 SAs were included; transfusions were performed in 2% (2/97) of primary SAs for OA or RCA. Increased transfusion rates occurred in PJI (23%, p = 0.0006) and fracture (18%, p = 0.0018) cases. The mean preoperative hemoglobin (Hgb) was 12.2 ± 2.2 with PJI, 12.0 ± 2.1 with fracture, and 13.3 ± 1.6 g/dL for all other SAs. Independent risk factors for transfusion included lower preoperative hemoglobin ( p < 0.001), PJI indication ( p = 0.008), and fracture indication ( p = 0.02), with no difference for fracture greater or less than 4 weeks old ( p = 0.53). Conclusion: Risk factors for allogeneic red blood cell transfusion after SA were low preoperative hemoglobin and procedures for PJI or fracture. Level of Evidence: Level III, retrospective case-control study